GRAPHICAL MODELLING OF A BUTT FUSION WELDING MACHINE FOR THERMOPLASTIC MATERIALS - Razvan - Petrisor Baroiu; Nicusor Baroiu; Georgiana - Alexandra Costin; Carmen - Catalina Rusu (Journal of Industrial Design and Engineering Graphics, 2020)
Welding is the process of merging two or more elements from metallic or thermoplastic materials, throught a heat or pressure source. The joining of the elements is ensured by the welded bead, which is a solidified quantity of material which allows the continuity of the crystalline structure of the material. In this paper, some basics about the welding of plastic materials are presented, as well as a 3D graphics modeling of a butt-welding machine achieved using Autodesk Inventor design environment. At the same time, in the software programme, the heating element modelling is carried out, namely, the electric hob with thermoregulator. This type of welding machine is used in a large number of applications and requires a proper design and dimensioning of the elements for ensuring reliability, strength, design flexibility, and low processing costs.